2021
DOI: 10.3389/fpsyt.2021.613764
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging as a Window Into the Pathophysiological Mechanisms of Schizophrenia

Abstract: Schizophrenia is a complex neuropsychiatric disorder with a diverse clinical phenotype that has a substantial personal and public health burden. To advance the mechanistic understanding of the illness, neuroimaging can be utilized to capture different aspects of brain pathology in vivo, including brain structural integrity deficits, functional dysconnectivity, and altered neurotransmitter systems. In this review, we consider a number of key scientific questions relevant in the context of neuroimaging studies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 120 publications
0
6
0
Order By: Relevance
“…Consistent with its role in neuroenergetics ( Shulman et al, 2014 , Singh, 2012 ), recent studies have revealed that cortical glutamate appears to play an important role in modulating the blood-oxygen level-dependent (BOLD) signal ( Enzi et al, 2012 , Kraguljac and Lahti, 2021 ) as well as the functional connectivity between brain regions ( Kraguljac et al, 2017 , Tomasi et al, 2013 ). In addition, a review of combined MRS/fMRI studies in healthy subjects concluded that there was evidence that cortical glutamate was not only correlated with the BOLD signal within the measured voxels, but also with regions distant from the voxel ( Duncan et al, 2014 ).…”
Section: Introductionmentioning
confidence: 86%
“…Consistent with its role in neuroenergetics ( Shulman et al, 2014 , Singh, 2012 ), recent studies have revealed that cortical glutamate appears to play an important role in modulating the blood-oxygen level-dependent (BOLD) signal ( Enzi et al, 2012 , Kraguljac and Lahti, 2021 ) as well as the functional connectivity between brain regions ( Kraguljac et al, 2017 , Tomasi et al, 2013 ). In addition, a review of combined MRS/fMRI studies in healthy subjects concluded that there was evidence that cortical glutamate was not only correlated with the BOLD signal within the measured voxels, but also with regions distant from the voxel ( Duncan et al, 2014 ).…”
Section: Introductionmentioning
confidence: 86%
“…Neuroimaging contributes a lot to the identification of clinically significant biological processes in schizophrenia and provides the opportunity to study specifics of the brain pathology in vivo, including structural brain abnormalities, impaired functional connectivity, and neurotransmitter systems disorders [18]. In many patients with schizophrenia, there are structural, functional, and metabolic disorders in the frontal lobe, yet the mechanisms underlying these changes are not yet fully understood [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, psychotic disorders showed the largest change in incidence rates in those with COVID-19 in both the present study and in Taquet et al [ 21 ]. While all psychiatric disorders are linked to stress, this pathophysiological connection is stronger for anxiety/depressive disorders than for psychotic disorders, where mechanisms affecting the brain structure and function seem to play a major role [ 36 ]. This might suggest that mechanisms elicited by SARS-CoV-2 infection, e.g., vascular dysfunction and neuroinflammation, could contribute to the development of new (or exacerbation of ongoing) mental/behavioral health symptoms, subsequently contributing to a diagnosis of psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%